Latent EBV enhances the efficacy of anti-CD3 mAb in Type 1 diabetes - Ana Lledó-Delgado; Paula Preston-Hurlburt; Lauren Higdon; Alex Hu; Eddie James; Noha Lim; S. Alice Long; James McNamara; Hai Nguyen; Elisavet Serti; Tomokazu S. Sumida; Kevan C. Herold (Nature Communications)
Abstract Teplizumab is approved for delaying the diagnosis of type 1 diabetes by modulating progression of disease. Compared to EBV-seronegative patients, those who are EBV-seropositive prior to treatment have a more robust response to teplizumab in two clinical trials. Here we compare the phenotypes, transcriptomes and development of peripheral blood cells before and after teplizumab treatment in participants. Higher number of regulatory T cells and partially exhausted CD8+ T cells are found in EBV-seropositive individuals than in EBV-seronegative controls at the baseline in the TN10 and AbATE trials. Mechanistically, single cell transcriptomics and functional assays identify the downregulation of NFκB and T cell activation pathways after treatment in EBV-seropositive patients; among diabetes antigen-specific CD8+ T cells, T cell receptor and mTOR signaling are also reduced. In parallel, signaling impairment is greater in adaptive than innate immune cells following teplizumab treatment in EBV-seropositive individuals. Our data thus indicate that EBV can impair signaling pathways in immune cells to modulate their responses in the context of type 1 diabetes.